“COMPLEX COMPOUNDS ZINCUM” (Scientific journal of the Fergana State University, 2024)
This article discusses the production of para-[di-1,4 - (4,4,4-trifluorobutanedione-1,3)]-benzene thiosemicarbazone, the result of elemental analysis, the forms of the tautomer, the structure and synthesis of its complex compound with the Zn 2+ ion. The resulting ligand, as well as the structure of the complex compound were determined by infrared (IR) spectroscopy. Zn2C16H16F6N8O2S2 the substance molecule has a bionuclear flat-square structure. the central atom has a coordination number of four, three places are occupied by N, O, S atoms, donors in the ligand molecule, and one place is occupied by an ammonia molecule. Para-[di-1,4-(4,4,4-trifluorobutanedione-1,3)]-benzene thiosemicarba-zone is considered important because it forms stable complex compounds with ions of most intermediate metals as a trident ligand held by donor atoms N, O, S. This is important because the ligand solves very important problems in the chemical industry. Among them are the isolation of rare earth metals, the analysis and treatment of industrial wastewater, the opening of solid soil, the production of medicines, the synthesis of biostimulants for agricultural crops, the manufacture of chemicals against plant pests.